2012
DOI: 10.3109/17453674.2012.733915
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in lumbar spinal stenosis surgery

Abstract: Background and purpose A considerable number of patients who undergo surgery for spinal stenosis have residual symptoms and inferior function and health-related quality of life after surgery. There have been few studies on factors that may predict outcome. We tried to find predictors of outcome in surgery for spinal stenosis using patient- and imaging-related factors.Patients and methods 109 patients in the Swedish Spine Register with central spinal stenosis that were operated on by decompression without fusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 33 publications
4
72
3
Order By: Relevance
“…Sigmundsson et al found in their prospective study that a smaller dural sac area predicted less leg pain postoperatively and more pain relief for LBP. However, they did not visually evaluate the severity of LSS, and walking distance was only subjectively estimated by the patient, depressive symptoms were not adjusted, and the clinical outcome was only evaluated with a one-year follow-up [20]. Our results are generally in line with these studies, i.e.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Sigmundsson et al found in their prospective study that a smaller dural sac area predicted less leg pain postoperatively and more pain relief for LBP. However, they did not visually evaluate the severity of LSS, and walking distance was only subjectively estimated by the patient, depressive symptoms were not adjusted, and the clinical outcome was only evaluated with a one-year follow-up [20]. Our results are generally in line with these studies, i.e.…”
Section: Discussionsupporting
confidence: 83%
“…Sigmundsson et al investigated the predictive value of MRI findings among a study population consisting of 109 LSS patients undergoing surgery with a one-year follow-up. They found in their prospective study that a smaller dural sac area predicted less leg pain postoperatively and more pain relief in low LBP [20]. None of these studies have, however, investigated the predictive value of visual and quantitative findings from preoperative lumbar spine MR images for both subjective and objective clinical outcome measures with a two-year follow-up [19], [20].…”
Section: Introductionmentioning
confidence: 99%
“…In the remaining 29 studies, patient characteristics were used as covariates, varying from 17 predefined covariates ( Royuela et al 2014 ) to adjustment for baseline PROMs only ( Solberg et al 2013 ). Adjustment for baseline PROMs was not performed in 8 studies ( Deer et al 2004 , Bridwell et al 2007 , Glassman et al 2009 , Zweig et al 2011 , Kovacs et al 2012 , Sigmundsson et al 2012 , McGirt et al 2013 , Adogwa et al 2014 ). In 8 studies, a dropout analysis was performed to compare baseline characteristics (missing data on assessment) with the remaining cases.…”
Section: Resultsmentioning
confidence: 99%
“…Second, we did not evaluate the duration of symptoms before surgery. Previous studies showed that duration of symptoms was associated with the clinical outcomes or PS 3,12,[19][20][21] ; however, some reviews have reported no association. 22,23 LSS symptoms are usually episodic, and patients do not always remember the onset.…”
Section: Discussionmentioning
confidence: 95%